The Circadian Clock Protein BMAL1 Acts as a Metabolic Sensor In Macrophages to Control the Production of Pro IL-1β - Timmons, George A.; Carroll, Richard G.; O’Siorain, James R.; Cervantes-Silva, Mariana P.; Fagan, Lauren E.; Cox, Shannon L.; Palsson-McDermott, Eva; Finlay, David K.; Vincent, Emma E.; Jones, Nicholas; Curtis, Annie M. (Frontiers in Immunology, 2021)
The transcription factor BMAL1 is a clock protein that generates daily or circadian rhythms in physiological functions including the inflammatory response of macrophages. Intracellular metabolic pathways direct the macrophage inflammatory response, however whether the clock is impacting intracellular metabolism to direct this response is unclear. Specific metabolic reprogramming of macrophages controls the production of the potent pro-inflammatory cytokine IL-1β. We now describe that the macrophage molecular clock, through Bmal1, regulates the uptake of glucose, its flux through glycolysis and the Krebs cycle, including the production of the metabolite succinate to drive Il-1β production. We further demonstrate that BMAL1 modulates the level and localisation of the glycolytic enzyme PKM2, which in turn activates STAT3 to further drive Il-1β mRNA expression. Overall, this work demonstrates that BMAL1 is a key metabolic sensor in macrophages, and its deficiency leads to a metabolic shift of enhanced glycolysis and mitochondrial respiration, leading to a heightened pro-inflammatory state. These data provide insight into the control of macrophage driven inflammation by the molecular clock, and the potential for time-based therapeutics against a range of chronic inflammatory diseases.